The Subcellular Location of Ovalbumin in Plasmodium berghei Blood Stages Influences the Magnitude of T-Cell Responses - Lin, Jing-Wen (Infect Immun, 2014)
Model antigens are frequently introduced into pathogens to study determinants that influence T-cell responses to infections. To address whether an antigen's subcellular location influences the nature and magnitude of antigen-specific T-cell responses, we generated Plasmodium berghei parasites expressing the model antigen ovalbumin (OVA) either in the parasite cytoplasm or on the parasitophorous vacuole membrane (PVM). For cytosolic expression, OVA alone or conjugated to mCherry was expressed from a strong constitutive promoter (OVA(hsp70) or OVA::mCherry(hsp70)); for PVM expression, OVA was fused to HEP17/EXP1 (OVA::Hep17(hep17)). Unexpectedly, OVA expression in OVA(hsp70) parasites was very low, but when OVA was fused to mCherry (OVA::mCherry(hsp70)), it was highly expressed. OVA expression in OVA::Hep17(hep17) parasites was strong but significantly less than that in OVA::mCherry(hsp70) parasites. These transgenic parasites were used to examine the effects of antigen subcellular location and expression level on the development of T-cell responses during blood-stage infections. While all OVA-expressing parasites induced activation and proliferation of OVA-specific CD8(+) T cells (OT-I) and CD4(+) T cells (OT-II), the level of activation varied: OVA::Hep17(hep17) parasites induced significantly stronger splenic and intracerebral OT-I and OT-II responses than those of OVA::mCherry(hsp70) parasites, but OVA::mCherry(hsp70) parasites promoted stronger OT-I and OT-II responses than those of OVA(hsp70) parasites. Despite lower OVA expression levels, OVA::Hep17(hep17) parasites induced stronger T-cell responses than those of OVA::mCherry(hsp70) parasites. These results indicate that unconjugated cytosolic OVA is not stably expressed in Plasmodium parasites and, importantly, that its cellular location and expression level influence both the induction and magnitude of parasite-specific T-cell responses. These parasites represent useful tools for studying the development and function of antigen-specific T-cell responses during malaria infection.